Caiman yacare (Yacare Caiman): Triplets - Vega, Gerardo Gabriel (2021)
The Broadsnouted Caiman (Caiman latirostris) and Yacare Caiman (Caiman yacare) are the two crocodilian species that inhabit Argentina (Prado et al. 2012. Cuad. Herpetol. 26. Suppl 1:403– 410). They can be easily differentiated based on species-specific morphological features (e.g., cranial and nuchal structures). These two species are broadly sympatric throughout their distribution in Argentina, although the C. latirostris appears to be allopatric across a larger area...